What influences employees to use enterprise social networks? A socio-technical perspective - (:unkn) unknown (Association for Information Systems (AIS), 2015)
The adoption of enterprise social network (ESN) for greater employee engagement and knowledge sharing practices within organisations is proliferating. However, ESN investments have thus far not resulted in expected gains in organisational benefits due to underutilisation by employees. Limited understanding of the implications of ESN use leads to a paucity of recommendations for effective use within an organisation. This research-in-progress paper seeks to determine the factors influencing the use of ESN among employees in a large Australian utility organisation, with the aim of contributing to a practical understanding of the key success factors of the use of this new workplace social platform. Our preliminary findings indicated that the employees’ ESN behaviour tends to be influenced by socio-technical factors, including technological (i.e. platform and content quality), organisational (i.e. top management support and ESN facilitating conditions), social (i.e. critical mass and communication climate), individual (i.e. perceived benefits, knowledge self-efficacy and time commitment) and task (i.e. task characteristics) factors. This paper concludes that a successful implementation of ESN in an organisation involves the nexus between these five factors and provides several recommendations about how ESN use can be enhanced.